Minimally Invasive Epicardial Injections Using a Novel Semiautonomous Robotic Device - Ota, Takeyoshi (2008)
BACKGROUND: We have developed a novel miniature robotic device (HeartLander) that can navigate on the surface of the beating heart through a subxiphoid approach. This study investigates the ability of HeartLander to perform in vivo semiautonomous epicardial injections on the beating heart. METHODS AND RESULTS: The inchworm-like locomotion of HeartLander is generated using vacuum pressure for prehension of the epicardium and drive wires for actuation. The control system enables semiautonomous target acquisition by combining the joystick input with real-time 3-dimensional localization of the robot provided by an electromagnetic tracking system. In 12 porcine preparations, the device was inserted into the intrapericardial space through a subxiphoid approach. Ventricular epicardial injections of dye were performed with a custom injection system through HeartLander’s working channel. HeartLander successfully navigated to designated targets located around the circumference of the ventricles (mean path length=51±25 mm; mean speed=38±26 mm/min). Injections were successfully accomplished following the precise acquisition of target patterns on the left ventricle (mean injection depth=3.0±0.5 mm). Semiautonomous target acquisition was achieved within 1.0±0.9 mm relative to the reference frame of the tracking system. No fatal arrhythmia or bleeding was noted. There were no histological injuries to the heart due to the robot prehension, locomotion, or injection. CONCLUSIONS: In this proof-of-concept study, HeartLander demonstrated semiautonomous, precise, and safe target acquisition and epicardial injection on a beating porcine heart through a subxiphoid approach. This technique may facilitate minimally invasive cardiac cell transplantation or polymer therapy in patients with heart failure.